Pengembangan dan Uji Usability Sistem Informasi Presensi Berbasis Web di Institusi Pendidikan - Eko Harry Pratisto; Daffa Mudia Athifah; Fendi Aji Purnomo (IJAI (Indonesian Journal of Applied Informatics), 2024)
Abstrak:Penelitian ini bertujuan mengembangkan sistem informasi presensi berbasis website untuk meningkatkan efisiensi dan akurasi pencatatan data kehadiran di sektor pendidikan. Sistem ini mendukung pencatatan kehadiran secara real-time yang dapat diakses dari berbagai perangkat yang terhubung ke internet, memudahkan pengguna seperti guru, siswa, dan pihak administrasi. Melalui pendekatan perancangan sistem berbasis Agile, penelitian ini melibatkan analisis kebutuhan, desain sistem menggunakan Entity-Relationship Diagram (ERD) dan Unified Modeling Language (UML), pengembangan, serta pengujian menggunakan metode usability testing. Hasil uji SUS menunjukkan nilai 82, 5 yang dapat diartikan sistem ini memiliki tingkat kemudahan penggunaan dan efisiensi yang baik, serta meningkatkan transparansi dan akuntabilitas pengelolaan kehadiran. =====================================================Abstract:This study aims to develop a web-based attendance information system to enhance the efficiency and accuracy of attendance data recording in the education sector. The system supports real-time attendance recording accessible from various internet-connected devices, facilitating users such as teachers, students, and administrative staff. Using an Agile system design approach, this study involves requirements analysis, system design utilizing Entity-Relationship Diagram (ERD) and Unified Modeling Language (UML), development, and testing through usability testing methods. The test result show 82,5 for SUS score which demonstrate that the system offers a high level of ease of use and efficiency while improving transparency and accountability in attendance management.The implementation of this system also shows a reduction in data input errors and an increase in the speed of attendance recapitulation compared to manual methods. However, challenges such as data security and technological infrastructure limitations in certain areas require attention. The web-based system is vulnerable to cyber threats, thus necessitating data security enhancements and infrastructure development to ensure its effectiveness.